Unprecedented dual binding behaviour of acridine group of dye: A combined experimental and theoretical investigation for the development of anticancer chemotherapeutic agents - Rajendran, Arivazhagan; Nair, Balachandran Unni (Biochimica et biophysica acta, 2006)
Acridine group of dyes are well known in the field of development of probes for nucleic acid structure and conformational determination because of their relevance in the development of novel chemotherapeutic agents, footprinting agents and for gene manipulation in biotechnology and medicine. Here, we report the interaction of 9- N,N-dimethylaniline decahydroacridinedione (DMAADD), a new class of dye molecule with calf thymus DNA (CT-DNA) which has been studied extensively by means of traditional experimental and theoretical techniques. The changes in the base stacking of CT-DNA upon the binding of DMAADD are reflected in the circular dichroic (CD) spectral studies. Competitive binding study shows that the enhanced emission intensity of ethidium bromide (EB) in presence of DNA was quenched by the addition of DMAADD indicating that it displaces EB from its binding site in DNA and the apparent binding constant has been estimated to be (3.3 ± 0.2) × 10 5 M − 1 . This competitive binding study and further fluorescence experiments reveal that DMAADD is a moderate binder of CT-DNA, while viscosity measurements show that the mode of binding is partial intercalation. Generally, one would expect increase in the melting temperature ( T m) of DNA in presence of intercalators. Interestingly, an unusual decrease in melting temperature (Δ T m of − 4 ± 0.2 °C) of DNA by the addition of DMAADD was observed. From our knowledge such a decreasing trend in melting point was not reported before for all the possible modes of binding. Molecular modeling gave the pictorial view of the binding model which clearly shows that of the various mode of binding, the dye prefers the major groove binding to the sites rich in GC residues and to the sites rich in AT residues it prefers intercalation mode of binding either through major or minor groove with the inclusion of the N,N-dimethylaniline (DMA) group inside the double helix which has been stacked in between the bases, under physiological relevant pH of 7.5.